Acquired Resistance to First‐Line Afatinib and the Challenges of Prearranged Progression Biopsies. Issue 11 (November 2016) - Campo, Meghan; Gerber, David; Gainor, Justin F.; Heist, Rebecca S.; Temel, Jennifer S.; Shaw, Alice T.; Fidias, Panos; Muzikansky, Alona; Engelman, Jeffrey A.; Sequist, Lecia V.
ABSTRACT : Objectives : The mechanisms of acquired resistance to the irreversible EGFR inhibitor afatinib are not well documented. We performed this prospective clinical trial to determine the prevalence of the mutation T790M in afatinib‐resistant patients. Methods : Eligible patients had EGFR mutations; they were tyrosine kinase inhibitor–naive and were treated with afatinib, 40 mg daily. At enrollment, patients consented to a future repeat biopsy at the time of acquired resistance. Results : A total of 24 patients were enrolled. The objective response rate was 58% (95% confidence interval [CI]: 37–78) with a median progression‐free survival of 11.4 months (95% CI: 5.9–13.7) and median overall survival of 20.8 months (95% CI: 15.1–40.5). Of the 24 patients enrolled, 23 progressed and only 14 completed repeat biopsy at time of progression, with 11 samples sufficient for molecular analysis. Of those 11 patients, four (36% [95% CI: 10.9–69.2]) harbored T790M. Conclusions : T790M is likely a common resistance mechanism in patients treated with first‐line afatinib. Although repeat biopsies at progression are crucial in elucidating resistance mechanisms, this study suggests that clinical and technical issues often limit their feasibility, highlighting the importance of developing noninvasive tumor‐genotyping strategies.